On universality of countable powers of absolute retracts - Banakh, T. O.; Radyl, Т. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct an absolute retract X of arbitrarily high Borel complexity such that the countable power X ω is not universal for the Borelian class A 1 of sigma-compact spaces, and the product X ω x ∑, where ∑ is the radial interior of the Hilbert cube, is not universal for the Borelian class A 2 of absolute G δσ-spaces.